Hubungan Konsumsi Jajanan Dengan Status Gizi Pada Siswa/I Sd N 90/Vi Durian Lecah Kabupaten Merangin - M. Ruswanda Zebua; Arnati Wulansari; Tina Yuli Fatmawati (Program Studi Gizi UNSIKA, 2024)
In general, school children have even ofien bought snacks sold in the canteen or around the school without realiziling that some of the snacks consumed can later endanger their health. There are two direc and indirect causes of nutrition problems. Natural causes such as foot and disease can directly cause malnutrition. This study aimed to determine the relationship between snack consumption and mutritional status in students of SD N 90/VI Durian Lecah, Merangin Regency. The study was a quantitative study with a cross-sectional research design. This research was conducted ar SD N 90/VI Durian Lecah, Merangin Regency, in June 2023. The population in this study amounted to 178 respondent. The sample of this study amounted to 70 respondent using simple random sampling technique. This research was conducted by distributing SQ-FQ questionnaires. The results showed that the most dominant frequencydistribution of respondent snack consumption was unfavourable to as many as 55 respondent (78.6%). The most dominant frequency distribution of respondent nutritional status was undernutrition, wits as many as 57 respondent (81.4%). In this study, it can be concluded that a significant relationship exists between snack consumption and nutritional status in student of SD N 90/VI Durian Lecah, Merangin Regency. Keyword : consumption snack, mutritional status